Modelagem matemática para otimização da produção agropecuária em uma unidade agropecuária no município de Serranópolis do Iguaçu - Pr - Santos, Lidinalva Rufino dos (2023)
Linear programming is being used in different sectors and its contribution is very important for rural producers to maximize the technical, economic and financial results of their production. This model can be used to assist in the production process in rural areas, for the reason that it allows the realization simulations and analysis of scenarios where it can be used. This work's main objective was to develop and analyze the application of linear programming as a tool to assist in agricultural production and its importance in decisionmaking in the productive sector of a small rural property. Through interviews, the approach allowed the collection of data that helped in the analysis of the production unit, the applied Mathematical Model contributed to the elaboration and proposition of development alternatives relevant to the reality in which it is intended to intervene. Based on the model developed and simulations carried out with data found in an agricultural production unit in the municipality of Serranópolis do Iguaçu, state of Paraná, it can be demonstrated that the program is effective in adapting production to current environmental legislation, as it provided a readjustment of the production system by controlling the number of pig batches produced in the year due to the excess phosphorus generated by pig manure that would pollute the soil, thus presenting a smaller quantity of batches and fertilizer supplementation through the purchase of phosphorus so that it does not exceed the permitted quantity.